Shaping the Academic Identity of Doctoral Students: Critical Factors and Influences (Journal of Educational Sciences, 2025)
The article examines how doctoral students in Kazakhstan develop their academic identity as future scholars. It explores critical factors that influence this process, including institutional, personal and socio-cultural elements. The research aims to understand how doctoral students’ academic identity develops throughout their PhD journey and to assess the role of mentorship, academic self-efficacy and international networks in shaping their identity as scholars. A mixed-method approach was employed, involving a survey of 150 doctoral students and semi-structured interviews with 20 participants. The results indicate that academic self-efficacy increases as students progress through their doctoral programs, with those in later stages exhibiting greater confidence in publishing and research. Mentorship was identified as a critical factor, with students who had constructive interactions with their supervisors reporting higher self-efficacy. Additionally, international exposure, such as attending conferences and collaborating with foreign researchers, significantly contributed to students’ academic identity. However, disparities were noted between disciplines, with students in the natural sciences experiencing more structured support and higher self-efficacy compared to those in the humanities and social sciences. These findings highlight the importance of providing strong mentorship and increasing opportunities for international engagements, particularly for students in fields with fewer resources, to better support the development of academic identity.Key words: academic identity, doctoral students, academic self-efficacy, mentorship, mixed-methods approach, publishing challenges.